Not even then : poems - Blanchfield, Brian, 1973- (New California poetry., 2004)
Not Even Then, the debut collection by Brian Blanchfield, introduces a poetry both compressed and musically fluid, beseechingly intimate and oddly authoritative. Blanchfield conducts readers through a unique, theatrical realm where concepts and personages are enlivened into action: Continuity, Coincidence, Symmetry, and Shame keep uneasy company there with Marcel Duchamp and Johnny Weissmuller, Lord Alfred Douglas and ""Blue Boy"" Master Lambton, Juliet's Nurse and Althusser's Moses. With its kinked and suspensive language, Not Even Then draws on the lyric tradition, even as it complicates that.